Coronary computed tomography angiography and its increasing application in day to day cardiology practice. Issue 1 (27th January 2016) - Markham, R.; Murdoch, D.; Walters, D. L.; Hamilton‐Craig, C.
Abstract: Coronary artery disease (CAD) is the leading single cause of death in Australia affecting around 1.4 million people. Coronary computed tomography angiography has an established role in the assessment of patients with low to intermediate pretest probability for CAD who have chest pain and is typically used with the aim to rule out significant coronary artery stenosis. Use was initially limited because of concerns over radiation exposure, a Medicare rebate restricted to specialist referrals and an absence of data supporting its use as an alternative to functional testing in patients with chest pain. Recent advances in scanner technology and image sequencing, along with data from randomised control trials, have addressed these issues and indicate that coronary computed tomography angiography will play a greater role in the assessment of CAD in the coming years.